2020
DOI: 10.1038/s41380-020-0679-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional imaging markers for susceptibility to psychosis

Abstract: The introduction of clinical criteria for the operationalization of psychosis high risk provided a basis for early detection and treatment of vulnerable individuals. However, about two-thirds of people meeting clinical high-risk (CHR) criteria will never develop a psychotic disorder. In the effort to increase prognostic precision, structural and functional neuroimaging have received growing attention as a potentially useful resource in the prediction of psychotic transition in CHR patients. The present review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 196 publications
3
53
0
1
Order By: Relevance
“…There is an ongoing debate about the concrete implications of risk predictions for members of CHR-groups. For a summary of the most important points in question, see Andreou and Borgwardt ( 19 ). For hippocampal volume to be of clinical use, a good cut-off margin between likely converters and non-converters will be required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is an ongoing debate about the concrete implications of risk predictions for members of CHR-groups. For a summary of the most important points in question, see Andreou and Borgwardt ( 19 ). For hippocampal volume to be of clinical use, a good cut-off margin between likely converters and non-converters will be required.…”
Section: Discussionmentioning
confidence: 99%
“…Studies had to assess CHR-status according to established criteria and the minimum follow-up period was to be 12 months, as adequate transition rates can be expected after this time ( 14 ). Another important factor for eligibility was the presence of the hippocampal volume as an absolute value and not in relation to other parts of the brain [as in voxel-based measurements (VBM)] because the latter values are not ideal for direct statistical comparison and may be compromised through position changes during image registration ( 19 , 60 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Widespread mild cognitive deficits are present in UHR individuals, falling at a level in between that of healthy individuals and those with confirmed SZ, and the magnitude of deficits is comparable with those at FHR ( 91 ). Further, abnormalities in brain activity and/or functional connectivity during a variety of cognitive tasks, including verbal memory and WM, verbal fluency, social cognition, as well as in the context of functions directly associated to the emergence of psychotic symptoms has also been shown [for a review, see Andreou and Borgwardt ( 92 )]. Of note and as was the results of the present review, neuroimaging abnormalities in UHR is observed even in the absence of differences in behavioral performance ( 92 ), which may point to a compensatory mechanisms for the brain circuits to uphold sufficient behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging techniques have received growing attention for studying brain alterations in affective disorders, which are associated with structural and functional abnormalities of the brain ( Bremner et al, 2002 ; Wu et al, 2016 , 2017 ; Wang et al, 2018 , 2019b , 2020 ; Andreou and Borgwardt, 2020 ). Magnetic resonance imaging (MRI) is a non-invasive method to characterize the brain structure and function in vivo ( Abe et al, 2010 ; Takamura and Hanakawa, 2017 ; Wang et al, 2019a ).…”
Section: Introductionmentioning
confidence: 99%